I had a question about the properties of logarithms and exponents, that I need some assistance on:

If you are familiar with electrical engineering principles, you may be familiar with Shannon's Channel Capacity Theorem:

$$C = W\log_2(1 + \text{SNR})$$

Where $W$ represents the bandwidth and $C$ is the capacity of the channel. Well it can be found such that

$$\text{SNR} = \dfrac{E_b}{N_0}\cdot \dfrac{C}{W}$$

If we take the above, and replace it into the original capacity equation, we get:

$$C = W \log_2\biggl(1 + \dfrac{E_b}{N_0}\cdot \dfrac{C}{W}\biggr) = W \cdot 2^{\bigl(1 +\frac{E_b}{N_0} \cdot \frac{C}{W}\bigr)}$$

However, this is where I'm kinda stuck. I would like to solve for $E_b/N_0$, but I'm a bit rusty on my algebra. This might be a rather simple question, but are there some properties of exponents or logs that I can leverage to solve for $E_b/N_0$?

Thanks for your help in advanced! I really appreciate it!

  • $\begingroup$ How did $\log_2 x$ become $2^x$? $\endgroup$ – parsiad Feb 12 '19 at 4:20
  • $\begingroup$ Is that not the proper way to remove a log? $\endgroup$ – Billy Thorton Feb 12 '19 at 4:23
  • $\begingroup$ I assume the claim you are using is $\log_2 x = 2^x$ for any $x > 0$, which is not true. See my answer below. $\endgroup$ – parsiad Feb 12 '19 at 4:29

Start with $$ C=W\log_{2}\left(1+\frac{E_{b}}{N_{0}}\frac{C}{W}\right). $$ Exponentiate both sides with base $2$ to get $$ 2^{C}=2^{W\log_{2}\left(1+\frac{E_{b}}{N_{0}}\frac{C}{W}\right)}. $$ Since $x\log_{y}z=\log_{y}(z^{x})$, it follows that $$ 2^{C}=2^{\log_{2}\left[\left(1+\frac{E_{b}}{N_{0}}\frac{C}{W}\right)^{W}\right]}. $$ Since $b^{\log_b x}=x$ for $x>0$, it follows that $$ 2^{C}=\left(1+\frac{E_{b}}{N_{0}}\frac{C}{W}\right)^{W}. $$ Now take roots of both sides to get $$ 2^{C/W}=1+\frac{E_{b}}{N_{0}}\frac{C}{W}. $$ You should be able to do the rest.


You have $$C = W \log_2(1 + SNR)\tag 1$$ $$SNR = \frac{E_b}{N_0} \frac{C} W\implies1+SNR=1+\frac{E_b}{N_0} \frac{C} W\implies\log_2(1+SNR)=\log_2\left(1+\frac{E_b}{N_0} \frac{C} W \right)\tag 2$$ Combine both equations and write $$C=W\log_2\left(1+\frac{E_b}{N_0} \frac{C} W \right)\implies \frac C W=\log_2\left(1+\frac{E_b}{N_0} \frac{C} W \right)\implies 2^{\frac C W}=1+\frac{E_b}{N_0} \frac{C} W $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.